Some evaluation methods for R&D projects and application orientations - Ninh, Tran Son (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Research and development (R&D) works have very high roles for sustainable development of organizations and enterprises. Therefore, R&D projects are established and implemented with diversified forms. With limited resources and prefixed development orientations, however, they should be evaluated in an adequate way. Various evaluation methods and models were proposed by scientists, each of them have its own strong points and weak ones. This report presents two methods popularly used and the combined one of them for a better integrated evaluation purpose. One of the purposes of this report is to combine qualitative indicators with variables in an optimal model. However, since the new model just passed some low scaled pilot works its weak points were not exploded. Therefore, the further steps targeted by the author are to test the methods for projects of larger scale to get a multi-aspect vision to the obtained results. Code: 13092601 <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">